Association of depression with gastroesophageal reflux disease, and the mediating role of risk factors: a Mendelian randomization study - Duan, Hui; Tao, Lan; Wu, Kaiwen; Li, Qian; Zhou, Xinxu; Dong, Peiwen; Sun, Xiaobin; Lin, Lin; Ma, Xiaolin; Zhao, Rong; Wang, Qiong (Frontiers in Psychiatry, 2024)
Background: Growing evidence suggests that depression affects gastroesophageal reflux disease (GERD). But, the relationship between depression and GERD is unclear. To examine the relationship between depression and the risk of GERD, as well as the mediating role of risk factors. Methods: We found genetic variants associated with GERD (N = 78,707) and depression (N = 500,199 (excluding 23 and Me) from the largest genome-wide association study and we applied twosample Mendelian randomization (MR) to find out if they are related. We further used two-step MR to find the mediating factors.Results: The results found a causal link between depression and GERD， inverse-variance weighted (IVW), risk OR 2.149 (95% CI, 1.910 to 2.418; P <0.001). F-statistics for all instrumental variables (IVs) were greater than 10. Multivariate MR maintained the significance of the depression-GERD link even after adjusting for body mass index (BMI), waist-to-hip ratio (WHR), and educational attainment (EA). Mediation analysis revealed that increased depression is associated with lower EA (OR = 0.94; 95% CI, 0.89 to 0.99; P = 0.03), while EA itself significantly impacts GERD risk (OR = 0.25; 95% CI, 0.18 to 0.34; P = 8.24 × 10⁻⁹). Ultimately, EA mediates the effect of depression on GERD (OR = 1.09; 95% CI, 1.01 to 1.18; P = 0.04), accounting for 11.4% of the mediated effect.Conclusions: Depression is associated with an increased risk of developing GERD, with some of the effects mediated by EA. This result may provide important information for the prevention and intervention of depression and GERD.